Pengaruh Tekanan Pemangku Kepentingan Terhadap Kualitas Laporan Keberlanjutan Perusahaan Di Indonesia - Kantohe, Meidy Santje Selvy; Kawulur, Hisky; Kosasih, Diah (Sekolah Tinggi Ilmu Ekonomi SBI, 2025)
This study aims to analyze the influence of employee pressure (Tkaryawan), consumer pressure (TKONS), and shareholder pressure (TPS) on the quality of sustainability reports (KLK) in energy companies in Indonesia. The results of the analysis show that employee pressure has a positive influence on the quality of sustainability reports. Meanwhile, consumer pressure and shareholder pressure do not affect the quality of sustainability reports. These findings provide important implications for companies in developing sustainability strategies that consider various pressures from stakeholders. Keywords: Employee Pressure, Consumer Pressure, Shareholder Pressure,Sustainability Report Quality